Evaluating the Effectiveness of mRNA-1273.815 Against COVID-19 Hospitalization Among Adults Aged ≥ 18 Years in the United States - Amanda Wilson; Neloufar Rahai; Ekkehard Beck; Elisha Beebe; Brian Conroy; Daina Esposito; Priya Govil; Hagit Kopel; Tianyi Lu; James Mansi; Morgan A. Marks; Katherine E. Mues; et al. (Infectious Diseases and Therapy)
Abstract Introduction In September 2023 the Food and Drug Administration (FDA) approved an updated mRNA COVID-19 vaccine targeting the XBB.1.5 sublineage. This study evaluates the effectiveness of mRNA-1273.815, a 2023–2024 Omicron XBB.1.5-containing mRNA COVID-19 vaccine in preventing COVID-19-related hospitalizations and medically attended COVID-19 in US adults aged ≥ 18 years. Methods This observational, matched cohort study used medical and pharmacy claims data from HealthVerity. Adults vaccinated with mRNA-1273.815 between September 12, 2023, and December 31, 2023, were followed through January 26, 2024. Vaccinated individuals were matched with individuals unvaccinated with any 2023–2024 COVID-19 vaccine on demographic and clinical characteristics. The primary and secondary outcomes were COVID-19 hospitalization and medically attended COVID-19, respectively. Inverse probability of treatment weighting and Cox proportional hazards regression were utilized to estimate vaccine effectiveness (VE). Results The study included 1,272,161 vaccinated individuals matched 1:1 with unvaccinated individuals, with a maximum follow-up of 128 (median 84) days. The VE against COVID-19 hospitalization was 51% (95% confidence interval [CI]: 48–54%). Subgroup analyses showed a VE of 56% (95% CI 51–61%) among adults ≥ 65 years and 46% (95% CI 39–52%) in immunocompromised adults. For medically attended COVID-19, the VE was 25% (95% CI 24–27%). Time-varying analyses showed that while VE declined over time, VE remained significant. Conclusion During the 2023–2024 respiratory season, the mRNA-1273.815 vaccine significantly protected against COVID-19-related hospitalizations and medically attended COVID-19 across diverse adult populations and demonstrated durability of the effect. These results support the continued use of updated COVID-19 vaccines to mitigate severe outcomes and maintain public health safety.